Supplemental Activity Sheets for Enhancing Learning in Electrical Installation and Maintenance Exploratory Subject - Macasinag, Jerwin Ocampo (Journal of Basic Education Research, 2026)
Purpose of the study: The purpose of this study is to design, develop, and validate supplemental activity sheets for the Exploratory Subject in Electrical Installation and Maintenance to enhance students’ competencies, engagement, and mastery of skills in alignment with the TLE curriculum standards in Basic Education. Methodology: A descriptive-developmental research design, guided by the modified ADDIE model, was employed to create Supplemental Activity Sheets using Canva for visual design. The DepEd Learning Resources Management and Development System (LRMDS) tool was used for evaluation by two TLE Master Teachers, two EIM teachers, and one licensed Master Electrician, with 5–16 years’ teaching, industry, and material development experience. Main Findings: The developed supplemental activity sheets in Electrical Installation and Maintenance were rated Very Satisfactory in content, format, presentation and organization, and accuracy and up-to-datedness by expert evaluators. The overall weighted mean was within the Very Satisfactory range, indicating high acceptability and alignment with the Most Essential Learning Competencies (MELCs). Novelty/Originality of this study: This study introduces contextually relevant, standards-aligned supplemental activity sheets for Electrical Installation and Maintenance, integrating MELCs, disaster risk reduction, gender equity, and higher-order thinking skills. By combining pedagogical design principles with visual learning strategies, it advances instructional resource development in TLE, offering a replicable model for enhancing competencies despite limited textbooks and specialized teaching staff.